Employment Effects of the Affordable Care Act Medicaid Expansions. Issue 2 (25th March 2018) - Leung, Pauline; Mas, Alexandre
Abstract : We examine whether the recent expansions in Medicaid from the Affordable Care Act reduced "employment lock" among childless adults who were previously ineligible for public coverage. We compare employment in states that chose to expand Medicaid versus those that chose not to expand, before and after implementation. We find that although the expansion increased Medicaid coverage by 3.0 percentage points among childless adults, there was no significant impact on employment.